Steamer CITY OF SEATTLE at dock, Skagway, Alaska, February 26, 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Steamer City of Seattle. Feb. 26 1900" Original photograph by Eric A. Hegg 820; copied by Webster and Stevens 49.A.